A germline-specific isoform of eIF4E (IFE-1) is required for efficient translation of stored mRNAs and maturation of both oocytes and sperm - Henderson, Melissa Anne; Cronland, Elizabeth; Dunkelbarger, Steve; Contreras, Vince; Strome, Susan; Keiper, Brett D. (East Carolina University, 2009)
Fertility and embryonic viability are measures of efficient germ cell growth and development. During oogenesis and spermatogenesis, new proteins are required for both mitotic expansion and differentiation. Qualitative and quantitative changes in protein synthesis occur by translational control of mRNAs, mediated in part by eIF4E, which binds the mRNAs 5 cap. IFE-1 is one of five eIF4E isoforms identified in C. elegans. IFE-1 is expressed primarily in the germ line and associates with P granules, large mRNPs that store mRNAs. We isolated a strain that lacks IFE-1 [ife-1(bn127)] and demonstrated that the translation of several maternal mRNAs (pos-1, pal-1, mex-1 and oma-1) was inefficient relative to that in wild-type worms. At 25°C, ife-1(bn127) spermatocytes failed in cytokinesis, prematurely expressed the pro-apoptotic protein CED-4/Apaf-1, and accumulated as multinucleate cells unable to mature to spermatids. A modest defect in oocyte development was also observed. Oocytes progressed normally through mitosis and meiosis, but subsequent production of competent oocytes became limiting, even in the presence of wild-type sperm. Combined gametogenesis defects decreased worm fertility by 80% at 20°C; ife-1 worms were completely sterile at 25°C. Thus, IFE-1 plays independent roles in late oogenesis and spermatogenesis through selective translation of germlinespecific mRNAs. Originally published Journal of Cell Science, Vol. 122, No. 10, May 2009
Keywords: Germ line; Protein synthesis; Maternal mRNAs; Oogenesis; Spermatogenesis; CED-4/Apaf-1; Meiosis; Polysomes